Piezoelectric catalytic material based on wood porous structure and preparation method thereof

By loading molybdenum disulfide and reducing graphene oxide on porous wood to form nanoheterojunctions, the problem of poor piezoelectric catalytic performance of porous wood-supported piezoelectric catalytic materials on organic dyes in the prior art is solved, and efficient dye degradation and good recycling rate are achieved.

CN119838612APending Publication Date: 2025-04-18HENAN AGRICULTURAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510064548.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing porous wood-loaded piezoelectric catalytic properties of the piezoelectric catalytic materials have poor piezoelectric catalytic properties on organic dyes and are difficult to achieve good recycling and reuse.

Method used

By loading molybdenum disulfide and reducing graphene oxide on porous wood, nanoheterojunctions are formed, which improves the conductivity of the material and carrier separation efficiency, thereby improving the piezoelectric catalytic performance.

Benefits of technology

It has achieved efficient degradation of organic dyes (such as methylene blue and rhodamine B) and has a high recycling rate. The degradation efficiency has only decreased by 15 to 25% after 8 to 10 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838612A_ABST
    Figure CN119838612A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of piezoelectric catalytic materials, and particularly relates to a piezoelectric catalytic material based on a wood porous structure and a preparation method of the piezoelectric catalytic material. The invention provides a piezoelectric catalytic material based on a wood porous structure. The piezoelectric catalytic material comprises wood with a porous structure, molybdenum disulfide and reduced graphene oxide, wherein the molybdenum disulfide and the reduced graphene oxide are loaded on the porous structure. Molybdenum disulfide, reduced graphene oxide, rGO and MoS2 are loaded on the porous wood to form a nano heterojunction, so that the porous wood has the characteristics of good conductivity and high carrier separation efficiency, carriers (electrons and holes) generated by MoS2 in the piezoelectric process can be effectively captured and transmitted, the piezoelectric catalytic performance of the porous wood is improved, and the preparation method is simple and easy to implement. Under normal-temperature and ultrasonic conditions, the composite material has relatively high degradation efficiency on organic dyes (methylene blue and rhodamine B), and has relatively high cyclic utilization rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of piezoelectric catalytic materials, and in particular to a piezoelectric catalytic material based on a porous wood structure and a preparation method thereof. Background Art

[0002] In order to alleviate the problems of environmental pollution and energy shortage, materials that can collect solar energy and mechanical energy have been widely studied in recent years. Among them, piezoelectric catalytic materials derived from the piezoelectric effect have received much attention in the field of water purification. The purification principle is that the piezoelectric material is subjected to force-induced deformation under the action of ultrasound or water flow, which triggers the piezoelectric effect and produces active species to degrade pollutants in water. However, the piezoelectric catalytic materials that are currently studied more are nanoparticles that are easy to agglomerate in aqueous solution and difficult to recycle and reuse. At the same time, nanoparticles can easily diffuse in natural water bodies and cause secondary pollution, which greatly limits their application in practical water treatment. In response to these limitations, researchers have explored different catalyst carriers to achieve good separation and recovery of catalysts. However, most carriers are not suitable for industrial applications due to the complex preparation steps and high cost. Wood, as a natural porous material, is inexpensive, renewable and easy to obtain. With its rich polar functional groups, open vertical channels and excellent mechanical strength, it is considered to be an excellent carrier for metal / inorganic nanocatalysts.

[0003] Molybdenum disulfide (MoS2) is a promising semiconductor piezoelectric material. Its single-layer or multi-layer structure shows ultra-high piezoelectric catalytic degradation activity for organic dyes under ultrasonic conditions, making it one of the best candidate materials to replace precious metal catalysts. However, MoS2 is prone to restacking during preparation and application. In addition, MoS2 itself has poor electrical conductivity, which leads to rapid recombination of electron-hole pairs, which also significantly reduces its piezoelectric catalytic performance. Many methods such as morphology-controlled synthesis, metal atom doping, and composite catalyst design have been used to improve the piezoelectric catalytic activity of MoS2.

[0004] In May 2023, Huo Bingjie et al. proposed a porous Ni / MoS2 / Wood bulk material for piezoelectric degradation of tetracycline in the article "Study on the Structural Regulation of Molybdenum Disulfide-Based Piezoelectric Materials and Their Antibiotic Degradation Performance". Specifically, the piezoelectric material MoS2 is encapsulated in the porous wood after the lignin is removed, and the metal nanoparticles Ni are introduced to improve its conductivity and provide active sites. The Ni / MoS2 / Wood bulk material is synthesized, and the piezoelectric response is triggered by ultrasonic vibration to degrade tetracycline micropollutants, showing a high degradation rate. After 5 consecutive piezoelectric catalytic tests, the degradation rate of tetracycline can still reach 90.20%, indicating that Ni / MoS2 / Wood has good reusability and stability. However, the piezoelectric catalytic material obtained above is for the piezoelectric catalytic degradation of tetracycline, and has not been applied to the catalytic degradation of organic dyes. Summary of the invention

[0005] The purpose of the present invention is to provide a piezoelectric catalytic material based on the porous structure of wood, so as to solve the problem that the existing porous wood-supported piezoelectric catalytic material has poor piezoelectric catalytic performance for organic dyes.

[0006] The second object of the present invention is to provide a method for preparing a piezoelectric catalytic material based on a porous wood structure, so as to solve the problem of poor piezoelectric catalytic performance of existing porous wood-loaded piezoelectric catalytic materials.

[0007] In order to solve the above technical problems, the technical solution of the piezoelectric catalytic material based on the porous structure of wood of the present invention is: A piezoelectric catalytic material based on a porous structure of wood. The piezoelectric catalytic material comprises wood with a porous structure and molybdenum disulfide and reduced graphene oxide loaded on the porous structure.

[0008] The present invention improves the prior art and provides a piezoelectric catalytic material based on the porous structure of wood. Molybdenum disulfide and reduced graphene oxide (rGO) are loaded on the porous wood. rGO and MoS2 form a nano heterojunction, which has the characteristics of good conductivity and high carrier separation efficiency. It can effectively capture and transmit the carriers (electrons and holes) generated by MoS2 in the piezoelectric process, thereby improving its piezoelectric catalytic performance.

[0009] The piezoelectric catalytic material based on the porous structure of wood provided by the present invention has a high degradation efficiency for organic dyes (methylene blue (MB), rhodamine B (RhB)) under normal temperature and ultrasonic conditions, and has a high recycling rate. After being recycled 8 to 10 times, its degradation efficiency only decreases by 15 to 25%.

[0010] In order to further improve the piezoelectric catalytic performance, preferably, graphene quantum dots are loaded on the porous structure of the wood. Graphene quantum dots (GQDs) and reduced graphene oxide can synergistically improve the conductivity of the catalytic material and further improve the piezoelectric catalytic performance.

[0011] In order to further improve the piezoelectric catalytic performance of the piezoelectric catalytic material, preferably, the loading rate on the porous structural wood is 25-30wt%.

[0012] The technical solution of the method for preparing the piezoelectric catalytic material based on the porous structure of wood of the present invention is: A method for preparing a piezoelectric catalytic material based on a porous structure of wood comprises the following steps: mixing a molybdenum source, a sulfur source, graphene oxide, and a reducing agent in a solvent to form a mixed solution, immersing the wood after lignin is removed in the mixed solution for a hydrothermal reaction, and washing and drying after the reaction is completed.

[0013] The present invention provides a method for preparing a piezoelectric catalytic material based on a porous structure of wood. The rGO and MoS2 nanoheterojunction is constructed in situ on the porous wood by a one-time hydrothermal synthesis method. The material has the characteristics of good conductivity and high carrier separation efficiency. In the in situ synthesis process, graphene oxide can inhibit the restacking of MoS2 nanosheets. The reduced graphene oxide (rGO) formed after the reducing agent reduces the graphene oxide can improve the conductivity of the catalyst and improve its piezoelectric catalytic performance.

[0014] In order to further improve the piezoelectric catalytic performance, preferably, the mixed solution includes graphene quantum dots, and the mass ratio of graphene oxide to graphene quantum dots is (1-2): 1. Molybdenum disulfide, graphene quantum dots and reduced graphene oxide obtained by reduction will form a hybrid, and the three will work synergistically to improve the conductivity of molybdenum disulfide, thereby improving the piezoelectric catalytic performance.

[0015] In order to further make the in-situ synthesis reaction of MoS2 more complete, preferably, the molar ratio of molybdenum in the molybdenum source to sulfur in the sulfur source is 1: (1.5~2).

[0016] In order to further improve the piezoelectric catalytic activity of the heterojunction formed by molybdenum disulfide and reduced graphene oxide, preferably, when the molybdenum source is ammonium molybdate tetrahydrate, (0.01-0.05) g of graphene oxide is added for every (0.25-0.3) g of molybdenum source; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is (2-2.5):1.

[0017] In order to further improve the reaction degree of the in-situ reaction, completely reduce the graphene oxide, and improve the in-situ synthesis efficiency of molybdenum disulfide, preferably, the temperature of the hydrothermal reaction is 180-200° C., and the time of the hydrothermal reaction is 18-24 hours.

[0018] In order to further improve the penetration efficiency of the mixed solution, preferably, the lignin is removed by immersing the wood in an acid solution for treatment, wherein the acid solution is obtained by adding sodium chlorite to a buffer solution formed by sodium acetate and acetic acid, the pH of the buffer solution is 4-5, and the mass fraction of sodium chlorite in the acid solution is 1-5%.

[0019] In order to further improve the removal efficiency of lignin, preferably, the temperature of the wood when immersed in the acid solution for treatment is 60-80° C. and the time is 8-12 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 These are photos of balsa wood after cutting, lignin removal, and in-situ synthesis in Example 2 of the present invention; Figure 2 This is a test result diagram of the degradation of methylene blue by the piezoelectric catalytic material based on the porous structure of wood according to the present invention; Figure 3 This is a graph showing the test results of the piezoelectric catalytic material based on the porous structure of wood of the present invention degrading Rhodamine B. DETAILED DESCRIPTION

[0021] The technical concept of the piezoelectric catalytic material based on the porous structure of wood provided by the present invention is as follows: The prior art loads MoS2 on porous wood and dopes it with metal nanoparticles Ni, which can improve the conductivity of the piezoelectric catalytic material, thereby improving the piezoelectric catalytic performance of the composite material. However, the present application loads molybdenum disulfide and reduced graphene oxide on porous wood, rGO and MoS2 form a nano-heterojunction, which can effectively improve the conductivity and carrier separation efficiency of the composite material, thereby improving the piezoelectric catalytic performance.

[0022] The method for preparing a piezoelectric catalytic material based on a porous wood structure provided by the present invention comprises the following steps: (1) Cut the wood into pieces and soak them in an acid solution for treatment. The acid solution is obtained by adding sodium chlorite to a buffer solution formed by sodium acetate and acetic acid. The pH of the buffer solution is 4-5, and the mass fraction of sodium chlorite in the acid solution is 1-5%. After the treatment is completed, the wood is washed and dried to obtain the treated wood.

[0023] (2) adding a molybdenum source and a sulfur source into water and stirring to form a molybdenum disulfide precursor solution, then adding graphene oxide and a reducing agent into water, stirring and ultrasonically dispersing to obtain a graphene oxide dispersion, mixing the molybdenum disulfide precursor solution and the graphene oxide dispersion to obtain a mixed solution, immersing the treated wood obtained in step (1) in the mixed solution for a hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 180-200° C., the time of the hydrothermal reaction is 18-24 hours, and after the reaction is completed, the wood is cleaned and dried.

[0024] In a specific embodiment, the wood is balsa wood, paulownia, birch or poplar, and the density of the wood is less than 0.5 g / cm 3 .

[0025] In a specific embodiment, the size of the wood after cutting in step (1) is 10 mm×10 mm×2 mm or 20 mm×20 mm×2 mm.

[0026] In a specific embodiment, in step (1), the wood is immersed in an acid solution for treatment to remove lignin, and the removal rate of lignin is 45-50%, which can ensure the mechanical properties of the piezoelectric catalytic material.

[0027] In a specific embodiment, the cleaning in step (1) is performed by rinsing with water, and the drying is performed by vacuum freeze drying.

[0028] In a specific embodiment, the sulfur source in step (2) is thiourea.

[0029] In a specific embodiment, when the mixed solution includes graphene quantum dots, the graphene quantum dots are added to the mixed solution in step (2) and stirred evenly.

[0030] In a specific embodiment, the mass concentration ratio of the molybdenum source to the solvent in the mixed solution is (0.25-0.3) g: (55-60) mL, and specifically, the solvent is water.

[0031] In a specific embodiment, the stirring time in step (2) is 20 to 30 minutes, and the ultrasonic dispersion time is 15 to 30 minutes.

[0032] In a specific embodiment, the washing in step (2) is performed by using water and ethanol to wash repeatedly 3 to 5 times alternately, and the drying is performed by vacuum freeze drying.

[0033] In a specific embodiment, the lignin removal rate after wood treatment is obtained by measuring the lignin content according to the Klason method.

[0034] The present invention is described in detail below in conjunction with specific examples. The raw materials used in the following examples are all conventional commercial products and are well known to those skilled in the art.

[0035] 1. Specific embodiments of the method for preparing the piezoelectric catalytic material based on the porous structure of wood according to the present invention Example 1 The preparation method of the piezoelectric catalytic material based on the porous structure of wood in this embodiment is as follows: (1) Preparation of acid solution: First prepare a sodium acetate-acetic acid buffer solution with a pH of 4.6, and then add sodium chlorite to the buffer solution to obtain an acid solution. The mass fraction of sodium chlorite in the acid solution is 1%.

[0036] (2) Wood pretreatment: The balsa wood was cut into blocks of 10 mm × 10 mm × 2 mm, and the blocks were immersed in the acid solution of step (1) to remove lignin. The treatment was carried out at a constant temperature of 80°C for 8 h, and the acid solution was replaced every 4 h. The lignin removal rate was controlled to be 45-50%. After the treatment, the blocks were taken out, rinsed thoroughly with water, and finally vacuum-frozen to obtain a porous wood sample (DW) with partially removed lignin.

[0037] (3) In situ synthesis: Weigh ammonium molybdate tetrahydrate ((NH)4Mo7O 24 ·4H2O) 0.29g, 0.248g thiourea (CH4N2S) in a beaker, add 30ml deionized water, stir until completely dissolved to form a molybdenum disulfide precursor solution; weigh 3.0g of 1.0wt% graphene oxide (GO) and 15mg of ascorbic acid (LAA) in another beaker, add 27ml deionized water, stir for 30min, and then ultrasonically disperse for 10min to obtain a graphene oxide dispersion; mix the solutions in the two beakers, stir evenly to obtain a mixed solution, transfer the mixed solution to a polytetrafluoroethylene reactor, add the porous wood sample (DW) obtained in step (2), and hydrothermally react at a temperature of 180°C for 24h. After cooling, take out the wood block and wash it alternately with deionized water and ethanol for 3 times, and freeze-dry to obtain a piezoelectric catalytic material rGO-MoS2 / DW.

[0038] The piezoelectric catalytic material prepared in this embodiment is the piezoelectric catalytic material based on the porous structure of wood provided by the present invention, including wood with a porous structure and molybdenum disulfide and reduced graphene oxide loaded on the porous structure.

[0039] Example 2 The preparation method of the piezoelectric catalytic material based on the porous structure of wood in this embodiment is as follows: Steps (1) to (2) are the same as those in Example 1.

[0040] (3) In situ synthesis: Weigh ammonium molybdate tetrahydrate ((NH)4Mo7O 24·4H2O) 0.29g, 0.248g thiourea (CH4N2S) in a beaker, add 30ml deionized water, stir until completely dissolved to form a molybdenum disulfide precursor solution; weigh 3.0g of 1.0wt% graphene oxide (GO) and 15mg of ascorbic acid (LAA) in another beaker, add 27ml deionized water, stir for 30min, and then ultrasonically disperse for 10min to obtain a graphene oxide dispersion; mix the solutions in the two beakers, stir evenly, and then add 30mg of graphene quantum dots (GQDs) to obtain a mixed solution, transfer the mixed solution to a polytetrafluoroethylene reactor, add the porous wood sample (DW) obtained in step (2), and hydrothermally react at 180°C for 24h. After cooling, take out the wood block and wash it alternately with deionized water and ethanol for 3 times, and freeze-dry to obtain the piezoelectric catalytic material GQDs-rGO-MoS2 / DW.

[0041] The piezoelectric catalytic material prepared in this embodiment is the piezoelectric catalytic material based on the porous structure of wood provided by the present invention, including wood with a porous structure and molybdenum disulfide, reduced graphene oxide and graphene quantum dots loaded on the porous structure.

[0042] Example 3 The preparation method of the piezoelectric catalytic material based on the porous structure of wood in this embodiment is as follows: Steps (1) to (2) are the same as those in Example 1.

[0043] (3) In situ synthesis: Weigh ammonium molybdate tetrahydrate ((NH)4Mo7O 24 ·4H2O) 0.29g, 0.248g thiourea (CH4N2S) in a beaker, add 30ml deionized water, stir until completely dissolved to form a molybdenum disulfide precursor solution; weigh 1.0g of 1.0wt% graphene oxide (GO) and 5mg of ascorbic acid (LAA) in another beaker, add 27ml deionized water, stir for 30min, and then ultrasonically disperse for 10min to obtain a graphene oxide dispersion; mix the solutions in the two beakers, stir evenly, and then add 10mg of graphene quantum dots (GQDs) to obtain a mixed solution, transfer the mixed solution to a polytetrafluoroethylene reactor, add the porous wood sample (DW) obtained in step (2), and hydrothermally react at 180°C for 24h. After cooling, take out the wood block and wash it alternately with deionized water and ethanol for 3 times, and freeze-dry to obtain the piezoelectric catalytic material GQDs-rGO-MoS2 / DW.

[0044] The piezoelectric catalytic material prepared in this embodiment is the piezoelectric catalytic material based on the porous structure of wood provided by the present invention, including wood with a porous structure and molybdenum disulfide, reduced graphene oxide and graphene quantum dots loaded on the porous structure.

[0045] Example 4 The preparation method of the piezoelectric catalytic material based on the porous structure of wood in this embodiment is as follows: Steps (1) to (2) are the same as those in Example 1.

[0046] (3) In situ synthesis: Weigh ammonium molybdate tetrahydrate ((NH)4Mo7O 24 ·4H2O) 0.29g, 0.248g thiourea (CH4N2S) in a beaker, add 30ml deionized water, stir until completely dissolved to form a molybdenum disulfide precursor solution; weigh 1.0wt% graphene oxide (GO) 5.0g and ascorbic acid (LAA) 25mg in another beaker, add 27ml deionized water, stir for 30min, and then ultrasonically disperse for 10min to obtain a graphene oxide dispersion; mix the solutions in the two beakers, stir evenly, and then add 50mg graphene quantum dots (GQDs) to obtain a mixed solution, transfer the mixed solution to a polytetrafluoroethylene reactor, add the porous wood sample (DW) obtained in step (2), and hydrothermally react at 200℃ for 18h. After cooling, take out the wood block and wash it alternately with deionized water and ethanol for 3 times, and freeze-dry to obtain the piezoelectric catalytic material GQDs-rGO-MoS2 / DW.

[0047] The piezoelectric catalytic material prepared in this embodiment is the piezoelectric catalytic material based on the porous structure of wood provided by the present invention, including wood with a porous structure and molybdenum disulfide, reduced graphene oxide and graphene quantum dots loaded on the porous structure.

[0048] 2. Experimental Examples The photos of the balsa wood after cutting, removing lignin, and in-situ synthesis in Example 2 are as follows: Figure 1 As shown, Figure 1 The middle (a) picture shows the balsa wood after it is cut into pieces. Figure 1 Figure (b) shows the photo after lignin removal. Figure 1 Figure (c) is a photograph after in-situ synthesis. It can be seen that molybdenum disulfide, reduced graphene oxide and graphene quantum dots are successfully loaded on the porous wood.

[0049] The porous wood sample (DW), GQDs-rGO-MoS2, and GQDs-rGO-MoS2 / DW prepared in Example 2 were subjected to thermogravimetric TG tests, and the test results are shown in Table 1. The loading rate of the porous wood sample (DW) was calculated according to the test results in Table 1, and the calculation method was: .

[0050] Among them, M1, M2 and M3 are the mass residual rates of DW, GQDs-rGO-MoS2 and GQDs-rGO-MoS2 / DW at 800°C in the thermogravimetric test, respectively. According to Table 1, the loading rate of GQDs-rGO-MoS2 / DW in Example 2 is 29.49%.

[0051] Table 1 TG test results of samples sample <![CDATA[T d max1 (℃)]]> <![CDATA[T d max2 (℃)]]> Mass residual rate (wt. %) 800 °C DW 310.4 439.1 1.67 <![CDATA[GQDs-rGO-MoS2]]> 532.8 713.9 30.36 <![CDATA[GQDs-rGO-MoS2 / DW]]> 291.4 475.6 10.13 The piezoelectric catalytic performance and recycling performance of the piezoelectric catalytic material prepared in the example were tested for organic dyes.

[0052] Piezoelectric catalytic performance test: prepare a methylene blue aqueous solution / rhodamine B aqueous solution with a concentration of 10 ppm, add the prepared piezoelectric catalytic material (the addition amount is 3 mg / mL), use ultrasound (40 Hz, 140 W) to trigger the piezoelectric degradation of methylene blue / rhodamine B, take samples every 10 min during ultrasonic degradation, and use a UV-visible spectrophotometer to test the absorbance changes of different samples to characterize the concentration changes of methylene blue.

[0053] Recycling performance test: After the prepared piezoelectric catalytic material was piezoelectrically degraded in a 10ppm methylene blue aqueous solution / rhodamine B aqueous solution for 40 minutes, the piezoelectric catalytic material was taken out, rinsed with water and dried at 60-80°C, and then placed in a methylene blue aqueous solution / rhodamine B aqueous solution of the same concentration for piezoelectric degradation again, and the degradation rate of each degradation was tested and calculated.

[0054] The piezoelectric degradation test results of the piezoelectric catalytic material of the present invention on methylene blue are as follows: Figure 2 As shown, Figure 2 Figure a in the figure is the UV-Vis curve of the piezoelectric degradation of methylene blue by rGO-MoS2 / DW in Example 1 at different times. Figure 2 Figure b is the UV-Vis curve of GQDs-rGO-MoS2 / DW in Example 2 for piezoelectric degradation of methylene blue at different times. Figure 2 The control in Figure a is without piezoelectric degradation; Figure 2 The horizontal axis of Figure a and Figure b is wavelength (nm), and the vertical axis is absorbance (Absorbance). Figure 2 It can be seen from Figure a and Figure b that the piezoelectric catalytic materials of Examples 1 and 2 both show good degradation effects on methylene blue, especially GQDs-rGO-MoS2 / DW shows better degradation efficiency.

[0055] Figure 2Figure c is the piezoelectric catalytic degradation curve of methylene blue by rGO-MoS2 / DW of Example 1 and GQDs-rGO-MoS2 / DW of Example 2. Figure 2 The horizontal axis of the c graph is time (Time, min), and the vertical axis is the concentration of methylene blue at a certain time C t The ratio of the initial concentration C0 to the initial concentration C0. It can be seen that compared with rGO-MoS2 / DW, GQDs-rGO-MoS2 / DW exhibits a higher degradation efficiency, and the degradation rate of rGO-MoS2 / DW within 40 min is 90.44%, and the degradation rate of GQDs-rGO-MoS2 / DW is 98.5%, indicating that GQDs-rGO-MoS2 / DW exhibits better piezoelectric catalytic performance for methylene blue.

[0056] Figure 2 Figure d is a bar chart showing the degradation rate of methylene blue after 8 cycles of degradation of GQDs-rGO-MoS2 / DW in Example 2. Figure 2 The horizontal axis of the graph d in FIG. 1 is the number of cycles (Cycles), and the vertical axis is the degradation rate (Degradation,%). It can be seen that after 8 cycles, the degradation rate can still reach 77.89%, indicating that the piezoelectric catalytic material of the present invention has good recycling performance for methylene blue.

[0057] The piezoelectric degradation test results of the piezoelectric catalytic material of the present invention on Rhodamine B are as follows: Figure 3 As shown, Figure 3 Figure a and Figure b are the UV-Vis curves of the piezoelectric degradation of Rhodamine B at different times by rGO-MoS2 / DW of Example 1 and GQDs-rGO-MoS2 / DW of Example 2, respectively. It can be seen that the piezoelectric catalytic material provided by the present invention also exhibits a good degradation effect on Rhodamine B. Compared with rGO-MoS2 / DW, GQDs-rGO-MoS2 / DW exhibits better degradation efficiency.

[0058] Figure 3 Figure c shows the piezoelectric catalytic degradation curve of rGO-MoS2 / DW in Example 1 and GQDs-rGO-MoS2 / DW in Example 2 for Rhodamine B. Within 40 min, the degradation rate of rGO-MoS2 / DW for Rhodamine B was 79.21%, and the degradation rate of GQDs-rGO-MoS2 / DW was 86.23%, indicating that GQDs-rGO-MoS2 / DW also exhibited better piezoelectric catalytic performance for Rhodamine B.

[0059] Figure 3Figure d is a bar chart of the degradation rate of Rhodamine B after 8 cycles of degradation by GQDs-rGO-MoS2 / DW in Example 2. It can be seen that after 8 cycles, the degradation rate can still reach 70.12%, indicating that the piezoelectric catalytic material of the present invention also has good recycling performance for Rhodamine B.

[0060] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A piezoelectric catalytic material based on a porous wood structure, characterized in that: The piezoelectric catalytic material comprises wood with a porous structure and molybdenum disulfide and reduced graphene oxide supported on the porous structure.

2. The piezoelectric catalytic material based on the porous structure of wood according to claim 1, characterized in that: The porous structure of the wood is loaded with graphene quantum dots.

3. The piezoelectric catalytic material based on the porous structure of wood according to claim 1 or 2, characterized in that: The loading rate on the porous structural wood is 25~30wt%.

4. A method for preparing a piezoelectric catalytic material based on a wood porous structure as claimed in claim 1, 2 or 3, characterized in that: The following steps are involved: A molybdenum source, a sulfur source, graphene oxide and a reducing agent are mixed in a solvent to form a mixed solution, the wood after lignin is removed is immersed in the mixed solution for a hydrothermal reaction, and after the reaction is completed, the wood is cleaned and dried.

5. The method for preparing a piezoelectric catalytic material based on a porous wood structure according to claim 4, characterized in that: The mixed solution includes graphene quantum dots, and the mass ratio of graphene oxide to graphene quantum dots is (1~2):

1.

6. The method for preparing a piezoelectric catalytic material based on a porous wood structure according to claim 4 or 5, characterized in that: The molar ratio of molybdenum in the molybdenum source to sulfur in the sulfur source is 1:(1.5~2).

7. The method for preparing a piezoelectric catalytic material based on a porous wood structure according to claim 6, characterized in that: When the molybdenum source is ammonium molybdate tetrahydrate, (0.01-0.05) g of graphene oxide is added for every (0.25-0.3) g of molybdenum source; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is (2-2.5):

1.

8. The method for preparing a piezoelectric catalytic material based on a porous wood structure according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 180-200° C., and the time of the hydrothermal reaction is 18-24 hours.

9. The method for preparing a piezoelectric catalytic material based on a porous wood structure according to claim 4, characterized in that: The removal of lignin is carried out by immersing the wood in an acid solution for treatment. The acid solution is obtained by adding sodium chlorite to a buffer solution formed by sodium acetate and acetic acid. The pH of the buffer solution is 4-5, and the mass fraction of sodium chlorite in the acid solution is 1-5%.

10. The method for preparing a piezoelectric catalytic material based on a porous wood structure according to claim 9, characterized in that: The temperature when the wood is immersed in the acid solution for treatment is 60~80℃ and the time is 8~12h.

Citation Information

Cited By

  • Selenium-doped layered mixed-phase molybdenum disulfide-based piezoelectric catalyst, preparation method and application

    CN121513909A